(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Hygienic mask use plays a significant role in effectively preventing contagious respiratory disease. COVID pandemic had made wearing masks mandatory for all. All need to follow mask hygienic practice to avoid respiratory infection. Though wearing a mask all time may also lead to discomfort and difficulties.Objective: The objective of the study was to assess the perception towards use of face mask among adultsMaterials and method: Conveniently 306 adults were chosen for conducting the study from UPHC Nayapalli and CHC Mendhasala of Khordha district. Participants were asked to fill the perception towards use of face mask (PEM tool)Results: 75.8% strongly agreed that wearing mask keeps a person safe from respiratory infections. 84.3% subjects strongly agreed for wearing a mask in public spaces. . Most 51% strongly disagree that face mask can make the person feel embarrassed. . 44.4% strongly disagree that its feel like to remove mask while talking.Conclusion: Present study shows that people are having good perception. They know the importance of mask wearing but sometime they are not able to follow the social guidelines due to various difficulties encountered while wearing mask. Continuous awareness programme is necessary to motivate them.